Influence of Physical and Morphological Factors On the Preference and Colonization of Bemisia Tabaci MED in Soybean Genotypes - Santana Lima, Ana Paula [UNESP] (2024)
The whitefly, Bemisia tabaci Mediterranean (MED), is an invasive pest of several crops, including soybeans. The objective of this study was to evaluate the resistance of soybean genotypes to B. tabaci MED, in addition to the influence of possibly related physical and morphological factors. A no-choice test was carried out with 90 soybean genotypes. Subsequently, 35 materials were selected for further no-choice and multiple-choice tests. Trichomes and leaf color of plants were observed, with the aim of correlating these factors with the preference and colonization of B. tabaci MED. The genotypes KS 4202, TMG 1188 RR, M 7739 IPRO, 65l65 IPRO, and PI 229358 were the least preferred by adults of B. tabaci MED. In the multiple-choice test, the lowest numbers of eggs and nymphs per square centimeter were observed for the genotypes Dowling, PI 229358, IAC 24, KS 4202. The genotypes IAC 19, TMG 1288 RR, TMG 1182 RR, 99R09, Dowling, and TMG 2375 IPRO presented the lowest numbers of eggs and nymphs in the no-choice assay. Plants with higher trichome density were preferred by adults of B. tabaci MED and, consequently, were more heavily colonized by these insects. Plants with leaves of lower luminosity and reduced green and yellow intensity were more attractive to the whiteflies. In summary, genotypes IAC 24, IAC 19, Dowling, 99R09, TMG 1182 RR, TMG 1288 RR and TMG 2375 IPRO exhibited lower colonization by B. tabaci MED in both assays, thus indicating their potential as promising sources of resistance to B. tabaci MED.